The New Liturgical Subjects of the 16th-Century Russian Painting - Onufrienko, Maksim O. (Actual Problems of Theory and History of Art, 2021)
The article deals with the earliest stage of the formation of liturgical scenes in Russian art. In the 16th century, several new subjects appear that depict the liturgy directly: Let All Human Flesh Be Silent, The Cherubikon, The Vision of St. Gregory the Theologian, Now the Powers of Heaven... etc. The first one appears in the conch of the central apse of the Moscow Kremlin Assumption Cathedral (1513–1515), which is believed to have been repeated in 1642–1643, when the cathedral was painted anew. A liturgical plot (perhaps The Vision of St. Gregory the Theologian) was also contained in the altar painting of the Chudov Monastery Cathedral in the Moscow Kremlin (1518–1519). If we assume the original system of painting was preserved during subsequent renovations, the iconography of specific scenes could reflect the tradition of their depiction in the middle but not in the beginning of the 16th century. In fact, the oldest extant Russian depiction of the Great Entrance is the scene of the Holy Divine Liturgy on the north iconostasis door of the Archangel Michael Church in Riga. This is a Pskov monument of the middle of the 16th century, now partially hidden by layers of late renovation, but with preserved iconography. It can be considered as a forerunner of the more complex scene The Cherubikon, common at the turn of the 17th century. All the liturgical plots can be found in the late 16th — early 17th centuries monuments. They have an established iconography, which, in one case, is based on the motif of the transfer of the Holy Gifts, borrowed from Byzantine monuments; in the other, the scene The Service of the Bishop was taken as a base. Apparently, all these subjects appear in different regions (Moscow, Pskov) almost independently of each other, although there is the possibility of their influence on each other.
Keywords: medieval Russian art; iconography; the Great Entrance; the Vision of Gregory the Theologian; liturgical plots; Orthodox liturgy